The evolution of life cycle complexity in aphids: Ecological optimization or historical constraint?. (15th June 2015) - Hardy, Nate B.; Peterson, Daniel A.; von Dohlen, Carol D.
<x xml:space="preserve">Abstract</x> For decades, biologists have debated why many parasites have obligate multihost life cycles. Here, we use comparative phylogenetic analyses of aphids to evaluate the roles of ecological optimization and historical constraint in the evolution of life cycle complexity. If life cycle complexity is adaptive, it should be evolutionarily labile, that is, change in response to selection. We provide evidence that this is true in some aphids (aphidines), but not others (nonaphidines)—groups that differ in the intensity of their relationships with primary hosts. Next, we test specific mechanisms by which life cycle complexity could be adaptive or a constraint. We find that among aphidines there is a strong association between complex life cycles and polyphagy but only a weak correlation between life cycle complexity and reproductive mode. In contrast, among nonaphidines the relationship between life cycle complexity and host breadth is weak but the association between complex life cycles and sexual reproduction is strong. Thus, although the adaptiveness of life cycle complexity appears to be lineage specific, across aphids, life cycle evolution appears to be tightly linked with the evolution of other important natural history traits.